2014
DOI: 10.1371/journal.pone.0083296
|View full text |Cite
|
Sign up to set email alerts
|

The G Protein-Coupled Estrogen Receptor (GPER) Is Expressed in Two Different Subcellular Localizations Reflecting Distinct Tumor Properties in Breast Cancer

Abstract: IntroductionThe G protein-coupled estrogen receptor (GPER) is a novel estrogen receptor that mediates proliferative effects induced by estrogen but also by tamoxifen. The aim of our study was to analyze the frequency of GPER in a large collective of primary invasive breast carcinomas, with special emphasis on the subcellular expression and to evaluate the association with clinicopathological parameters and patient overall survival.MethodsThe tissue microarrays from formalin-fixed, paraffin embedded samples of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 52 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…The debate on the subcellular location of GPER is ongoing, with varying reports showing cell surface (49), intracellular membrane (154), and even nuclear localization (155). Moreover, receptor location may influence pathologies such as breast cancer, where the receptor resides in the nucleus of MCF7 cells but the cytoplasm of T47D breast cancer cells (156). The signaling pathways activated by GPER are also varied and opposing.…”
Section: The Future Of Gpermentioning
confidence: 99%
“…The debate on the subcellular location of GPER is ongoing, with varying reports showing cell surface (49), intracellular membrane (154), and even nuclear localization (155). Moreover, receptor location may influence pathologies such as breast cancer, where the receptor resides in the nucleus of MCF7 cells but the cytoplasm of T47D breast cancer cells (156). The signaling pathways activated by GPER are also varied and opposing.…”
Section: The Future Of Gpermentioning
confidence: 99%
“…This was to such a degree that it has been questioned whether – and how – ethnoracial classification in Brazil correlates with genomic ancestry. Previous genome studies based on up to a hundred informative markers showed conflicting results on this correlation345678.…”
mentioning
confidence: 95%
“…E2 stimulation of cells expressing GPER but lacking ERα activates the MAPK and PI3K cascades, among other pathways, increasing proliferation of many breast cancer cell lines, suggesting GPER may play a role in one or more events of breast carcinogenesis (15-17) and particularly triple negative breast cancer (18, 19). A small number of retrospective studies has examined the relationship between GPER expression in breast tumor samples and clinical outcome or its correlates.…”
Section: Introductionmentioning
confidence: 99%
“…Another investigation demonstrated an increased recurrence rate in GPER + invasive ductal breast cancers (21). More recently, a study of invasive breast cancer samples demonstrated GPER expression is an independent prognostic factor for decreased disease-free survival in patients treated exclusively with tamoxifen (22), with its cellular localization potentially playing a critical role (18). While these studies suggest a role for GPER in breast cancer, to this point no direct experimental evidence demonstrates a functional role for GPER in the initiation and/or progression of breast cancer.…”
Section: Introductionmentioning
confidence: 99%